Foundations of mechanics of corroding materials - Hoffman, T.J.; Niechciałkowska, B. (Archives of Mechanics, 1999)
In this paper the basic principles of mechanics concernning the balance laws of the corrosion process models are presented. The corrosion process has been described by a linear law of creation of the oxide layer using a single corrosive rate constant. The mass defect is neglected in the balance law of mass. In the balance of momentum, the corrosion processes are treated as a source of the additional compressive stresses. The kinematic magnitudes are treated independently of the corrosion processes. This approach is based on the infinitesimal strains and linear constitutive equations. Two linear versions of the theory, which are from the formal point of view certain variants of the Coupled Fields Theory, have been proposed. The first of them includes the corrosive term in the displacement equation of motion and has no mechanical term in the equation of corrosion. The second of them contains the coupling terms, both in the equation of motion and in the equation of corrosion.